The Business Analysis of Catfish (Clarias sp) Enlargement on Fish Pond In Sub-District of Minas, District of Siak, Riau Province - Yulianti, Sari; Yulinda, Eni; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research about the business analysis of catfish (Clarias sp) enlargement on fish pond was conducted on January, 2016 in Sub-District of Minas, District of Siak, Riau Province. This study aims to (1) analyzed the business enlargement of fish pond of catfish and (2) the feasibility business of enlargement of fish pond of catfish. The method used is a survey method that includes observation, interviews and documentation.Based on the results of research (1) the average production costs incurred in enlargement business of catfish with an area of 72-220 m2 of Rp 5.687.750, - / harvest up to Rp 16.788.250, - / harvest with total receipts received by Rp 15.912 million, - / harvest up to Rp 36.21 million, - / harvest and great benefits received Rp 8.7 million,-/ harvest up to Rp 21 million, - / harvest and (2) enlargement business of fish pond of catfish in Minas feasible with RCR value> 1, the FRR values> 6.02% and the value of PPC is between 1,94 to 4,67 per period or ± 6 to 14 month. Keywords : Enlargement Lele, The Business Analysis, Sub-Districk of Minas